Pronunciation of Syafatain in Surah Al-Fatihah: Phonetic Analysis of The Imam of The Mosque - Muhammad Dhiya Alwan; Hikmah Maulani (Al-Fusha : Arabic Language Education Journal, 2023)
Arabic has a specific pronunciation and has the potential to change meaning if it is not pronounced correctly. This study oriented to analyze the characteristics of the pronunciation of the Syafatain makhārijul huruf in surah Al-Fatihah by the imam of a mosque in Sukasari sub-district when leading prayers and to identify phonological errors made. The research method used was descriptive with a qualitative approach. To collect research data, the methods used were listening methods, interviews, and documentation in the form of recordings of the voice of the imam of the mosque when reciting surah Al-Fatihah. The results of this study indicated that the characteristics of the imam of the mosque in reciting surah Al-Fatihah were quite diverse and there are phonological errors made by the imam of the mosque in reciting the letter ب, especially Al-Fatihah when the letter is in the middle of the word segmentation level. Any Arabic pronunciation needs to follow phonological conventions so that the Arabic sounds occupy the appropriate positions.